Z zimną wojną w tle. Polska wobec stosunków dwustronnych z RFN w latach 1956-1981 = Against the cold-war backdrop: Polish relationships with West Germany over the period of 1956-1981 - Jarząbek, Wanda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper's purpose is to show the changing attitude of the Polish authorities towards German Federal Republic over the period of 1956-1981: Warsaw's expectations concerning the establishment of diplomatic relations and their normalisation. Besides, this paper discusses the factors limiting the possibility of reaching agreements satisfying for both sides.
Keywords: stosunki polsko-niemieckie; Polska Rzeczpospolita Ludowa; Niemiecka Republika Federalna; historia - 1945-1989